Alte Idee, neues Programm: Der Gründungszuschuss als Nachfolger von Überbrückungsgeld und Ich-AG - Marco Caliendo; Jens Hogenacker; Steffen Künn; Frank Wießner (Journal for Labour Market Research, 2012)
– The promotion of self-employment as part of active labour market policy ranks as one of the most important support schemes in Germany. The main idea is to grant unemployed individuals financial support to start their own business and therefore to escape unemployment. For this purpose two schemes provided financial support to the unemployed until 2006, the bridging allowance ('Überbrückungsgeld') and the start-up subsidy ('Existenzgründungszuschuss'). Although both programs have been shown to be very effective, the German government replaced both schemes by one single program, the new start-up subsidy ('Gründungszuschuss', GZ) in August 2006, mainly to reduce bureaucratic burden. This study aims at providing descriptive evidence on participant's structure of the new instrument in comparison to the former programs. Moreover, we shed light on business survival, income situation of founders and job creation by the new businesses. Results show that new program (GZ) supports a smaller range of unemployed individuals than initially subsidized by the former two schemes. However, we do not find indication that individuals exhaust their unemployment benefit entitlement before entering the program. With respect to sustainability we find that 75-84% of subsidized businesses are still self-employed 19 months after start-up and household income can be considered to secure the livelihood. Finally, with the data at hand we are able to contribute new insights to the discussion about potential deadweight effects associated with business subsidies. We show that those effects indeed exist but to a smaller extent than previously assumed.
Keywords: J68; M13; H43; 330; Unternehmensgründung - Förderung; Gründungszuschuss - Erfolgskontrolle; Existenzgründungszuschuss; Überbrückungsgeld; Wirkungsforschung; arbeitsmarktpolitische Maßnahme; Arbeitslose; Ich-AG